(untitled) (Bangladesh Heart Journal, 2021)
Background: The Coronavirus Disease 2019 (COVID-19) pandemic is a significant challenge particularly for low and middle-income countries like Bangladesh. Interventions such as home isolation, frequent hand washing, wearing face mask, maintaining social distancing are difficult to implement in densely populated areas. The aim of the study was to delineate demographics, clinical manifestations, treatment modalities and outcomes of COVID-19 affected patients of our hospital. Methods: This prospective observational study was carried out at National Heart Foundation Hospital & Research Institute of Bangladesh between 08 March 2020 to 07 March 2021. During this period all admitted patients who subsequently were diagnosed as COVID positive and health care personnel of this hospital, who experienced fever or respiratory symptoms or came in close contact with COVID-19 patients at home or their workplace & become COVID positive were included. Results: During this one-year period a total of 769 COVID positive patients were detected in our hospital. Mean age of the patients was 48.16 ±15.63 years (range 1-92 years). Two third were male (64.9% vs 35.1%) and had multiple co-morbidities. One fifth of the patients were (19%) asymptomatic. The mean duration of onset of symptoms to test was 3.72±3.7 days. Most common symptoms were fever (65.3%), cough (37.1%), shortness of breath (33.6%) and fatigue (27.8%). Other symptoms were bodyache (18.6%), headache (16.6%), anosmia 16%), sore throat (12.1%), diarrhoea (6.8%), dizziness (5.3%), generalized itching (3.8%). Nearly two third of the COVID positive patients (63.2%) had a diagnosed cardiovascular disease at onset and remaining 36.8% patients presented with only COVID-19 disease. About 75% patients received ivermectin, 5.1% patients received favipiravir and 4.4% patients received remdesivir. Three fourth (74.38%) of patients were hospitalized and remaining one fourth (25.62%) patients were treated either in home isolation or in institutional isolation. Most of the patients recovered, with a case fatality rate of 3.5%. Diabetes, hypertension and age ≥50 years were the independent predictors of mortality. Conclusion: Although most of the patients had good outcome the study revealed 3.5% case fatality. Male with multiple co-morbidities were predominantly affected by COVID 19. Fever, cough, shortness of breath and fatigue were common presenting symptoms. Bangladesh Heart Journal 2021; 36(2): 89-97